Bureaucracy and Administration - EVAN M. BERMAN, JACK RABIN (Taylor & Francis, 2009)
HISTORICAL ANTECEDENTS ON BUREAUCRACY THEORETICAL AND CONCEPTUAL PERSPECTIVES ON BUREAUCRACY AND BUREAUCRATIC POLITICS BUREAUCRACY AND PUBLIC MANAGEMENT BUREAUCRACY AND BUREAUCRATIC POLITICS IN THE AMERICAS BUREAUCRATIC POLITICS IN EUROPE BUREAUCRATIC POLITICS IN ASIA AND THE MIDDLE EAST BUREAUCRACY AND BUREAUCRATIZATION, CHANGE AND REVOLUTION